CHARACTERISTICS AND VARIABILITY OF SENTINEL-1A OBSERVATION INTERNAL WAVES: POLICY IN THE MANAGEMENT OF THE HALMAHERA MARINE AREA, NORTH MALUKU (2015-2023) - Rohani, Siti; Nurjaya, I Wayan; Naulita, Yuli; Karang, I Wayan Gede Astawa (Jurnal Penelitian Perikanan Indonesia, 2025)
The waters of Halmahera, North Maluku have potential for the formation of internal waves. The uneven topographic conditions act as a trigger for the generation of internal waves. The Sentinel-1A Synthetic Aperture Radar (SAR), with its advantage of being unaffected by clouds and usable in various weather conditions, is capable of mapping the location of formation and the propagation characteristics of internal waves. The aim of this study is to understand the characteristics and variability of internal waves in the waters of Halmahera, North Maluku. SAR analysis results from the period 2015-2023 show that the dominant generation of internal waves occurs in the south of Halmahera, namely Obi Island, and also in the northeast of Halmahera, namely the Weda Strait, resulting in 74 packets being successfully identified. High interannual variability occurred in 2019, whereas high seasonal variability occurred in the eastern season, namely August. The characteristics of internal wave parameters revealed a maximum phase speed of 4.88 m/s and a minimum of 0.19 m/s, predominantly occurring during the rising tide, when the tide reaches 0.60 meters and the ebb -0.06 meters. The interaction of tides and topography results in density stratification in the thermocline layer at depths of less than 200 meters.